2019
DOI: 10.1159/000499183
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity and Metabolic Alterations in Medial Prefrontal Cortex in a Rat Model of Fetal Alcohol Spectrum Disorder: A Resting-State Functional Magnetic Resonance Imaging and in vivo Proton Magnetic Resonance Spectroscopy Study

Abstract: Prenatal ethanol exposure alters brain structure, functional connectivity, and behavior in humans and rats. Behavioral changes include deficits in executive function, which requires cooperative activity between the frontal cortices and other brain regions. In this study, we analyzed the functional connectivity and neurochemical levels of the prefrontal cortex (PFC) using resting-state functional magnetic resonance imaging (rsfMRI) and proton magnetic resonance spectroscopy (1H-MRS) in ethanol-exposed (Eth) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…We then analyzed males and females separately to determine differences between treatment groups within sex. Previous work from our group found sex differences in both behavioral and rs-fMRI measures in our models of FASD [20,21]. Trials to criterion of each of the 6 phases was the dependent variable, and experimental group was the between-group variable.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…We then analyzed males and females separately to determine differences between treatment groups within sex. Previous work from our group found sex differences in both behavioral and rs-fMRI measures in our models of FASD [20,21]. Trials to criterion of each of the 6 phases was the dependent variable, and experimental group was the between-group variable.…”
Section: Discussionmentioning
confidence: 82%
“…One of the most consistent findings across rodent models with various means of delivery, concentrations, and timing of prenatal alcohol exposure is poor executive function and cognitive flexibility. The neurological underpinnings of cognitive deficits point to poor prefrontal cortex organization, and dysregulated functional cooperation between the frontal cortices and striatum (e.g., [17,19,20]). This sensitivity to ethanol exposure persists from the prenatal phase to adolescence [19,63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other resting state fMRI research conducted with rats exposed to prenatal alcohol has also revealed sex-dependent alterations in connectivity. Using a seed-based approach, Tang and colleagues showed baseline sex-dependent differences in functional connectivity among controls and a sex-by-alcohol interaction in cortico-striatal connectivity (Tang et al, 2019). In a subsequent investigation relying on a graph theory approach, the same research group found altered network organization in females, but not males, following PAE (Tang, Xu, Zhu, Gullapalli, & Mooney, 2020).…”
Section: Discussionmentioning
confidence: 99%